Spatiotemporal Pattern of Ectopic Cell Divisions Contribute to Mis-Shaped Phenotype of Primary and Lateral Roots of katanin1 Mutant - Ovečka, Miroslav; Luptovčiak, Ivan; Komis, George; Šamajová, Olga; Samakovli, Despina; Šamaj, Jozef (Frontiers in Plant Science, 2020)
Pattern formation, cell proliferation and directional cell growth, are driving factors of plant organ shape, size and overall vegetative development. The establishment of vegetative morphogenesis strongly depends on spatiotemporal control and synchronization of formative and proliferative cell division patterns. In this context, the progression of cell division and the regulation of cell division plane orientation are defined by molecular mechanisms converging to the proper positioning and temporal reorganization of microtubule arrays such as the preprophase microtubule band, the mitotic spindle and the cytokinetic phragmoplast. By focusing on the tractable example of primary root development and lateral root emergence in Arabidopsis thaliana, genetic studies have highlighted the importance of mechanisms underlying microtubule reorganization in the establishment of the root system. In this regard, severe alterations of root growth and development found in extensively studied katanin1 mutants of Arabidopsis thaliana (fra2, lue1 and ktn1-2), were previously attributed to defective rearrangements of cortical microtubules and aberrant cell division plane reorientation. How KATANIN1-mediated microtubule severing contributes to tissue patterning and organ morphogenesis, ultimately leading to anisotropy in microtubule organization is a trending topic under vigorous investigation. Here we addressed this issue during root development, using advanced light-sheet fluorescence microscopy (LSFM) and long-term imaging of ktn1-2 mutant expressing the GFP-TUA6 microtubule marker. This method allowed spatial and temporal monitoring of cell division patterns in growing roots. Analysis of acquired multidimensional data sets revealed the occurrence of ectopic cell divisions in various tissues including the calyptrogen and the protoxylem of the main root, as well as in lateral root primordia. Notably the ktn1-2 mutant exhibited excessive longitudinal cell divisions (parallel to the root axis) at ectopic positions. This suggested that changes in the cell division pattern and the occurrence of ectopic cell divisions contributed significantly to pleiotropic root phenotypes of ktn1-2 mutant. LSFM provided evidence that KATANIN1 is required for the spatiotemporal control of cell divisions and establishment of tissue patterns in living A. thaliana roots.